2018
DOI: 10.1088/1361-648x/aac46d
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of strain-induced Jahn–Teller distortions in BaFeO3

Abstract: The effect of epitaxial strain on structural, magnetic and electronic properties of BaFeO perovskite oxide are investigated from first principles calculations, using the density functional theory (DFT) plus the Hubbard approach (DFT+U) within the generalized gradient approximation. Hybrid functional calculations, based on mixed exact Hartree-Fock and DFT exchange energy functionals, are also performed. For the ground state calculations, the DFT+U is found more suitable to describe the half metallic and ferroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…For comparison, similar calculations were performed on cubic Pm 3̅ m BaFeO 3 . Previous ab initio simulations found that, within the collinear spin polarization, the FM phase is thermodynamically more stable than the AFM phases at 0 K for BaFeO 3 , and we therefore focus on the FM phase for BaFeO 3 . The reciprocal space of the five-atom cubic primitive unit cell was sampled by a Γ-centered 12 × 12 × 12 mesh; otherwise, the same computational conditions as for Ba 3 Fe 3 O 8 were applied.…”
Section: Methodsmentioning
confidence: 99%
“…For comparison, similar calculations were performed on cubic Pm 3̅ m BaFeO 3 . Previous ab initio simulations found that, within the collinear spin polarization, the FM phase is thermodynamically more stable than the AFM phases at 0 K for BaFeO 3 , and we therefore focus on the FM phase for BaFeO 3 . The reciprocal space of the five-atom cubic primitive unit cell was sampled by a Γ-centered 12 × 12 × 12 mesh; otherwise, the same computational conditions as for Ba 3 Fe 3 O 8 were applied.…”
Section: Methodsmentioning
confidence: 99%
“… a The presence or absence of JT distortions is also sensitive with regard to the computational details of the calculations. The balance between the cubic and JT distorted structures was shown to be dependent on the employed exchange–correlation functional …”
mentioning
confidence: 99%
“…Phase Method U eff (eV) Stability 2017 [14] cub. BaFeO3 DFT+U 5 Stable 2018 [16] cub. BaFeO3 DFT+U 4 Unstable 2018 [15] cub.…”
Section: Yearmentioning
confidence: 99%
“…The specific U eff value is not trivial to determine and, as Table I reveals, a small change can lead to qualitatively different results. For example, cubic BaFeO 3 was predicted to be dynamically stable with U eff ≈ 5 eV [14,15], while Jahn-Teller distortions were observed with U eff = 4 eV [16,17]. These differences highlight that the U eff value needs to be chosen with care, ideally by calibration with respect to a higher level method.…”
Section: Yearmentioning
confidence: 99%
See 1 more Smart Citation